Os modos de vida da população em situação de rua : narrativas de andanças nas ruas de Vitória/ES - Kunz, Gilderlandia da Silva (2012)
This work aimed to study the ways of life of the homeless population that inhabits the city of Vitoria/Espírito Santo. The research we developed encompassed three stages: a first stage, which we designate as an exploratory study, conducted in the downtown area of Vitória/ES, aimed to get closer from the groups of homeless people to map the formal and informal policies that cross the life in the streets; a second stage aimed to map the groups on the streets in the city of Vitória, highlighting the urban landscapes in which this population makes social relations; a third stage in which, from the mapping done, the groups were defined from which we selected the homeless people we talked to, in order to give visibility to the tactics and gimmicks that they weave into their daily life. We emphasize that the research provided to notice that the homeless population reinvents spaces and objects in their daily life on the streets, dodging bans and limits, re-signifying objects, places and uses, as well as producing various designs in the urban tissue. The survey also highlighted the practices of intolerance and violence against the homeless population, as well as the violation of their social and political rights